(untitled) (International journal of artificial intelligence, 2025)
This article examines the influence of Gafur Ghulam on Uzbek poetry through literary criticism and research. The study analyzes the poet's creative heritage, his contribution to modern Uzbek poetry, and his impact on other poets' works based on literary analysis and scholarly perspectives.